Complicated grief: A systematic review of the prevalence, diagnosis, risk and protective factors in the adult population of Spain. - Parro-Jiménez, Elena; Morán, Noelia; Gesteira, Clara; Sanz, Jesús; García-Vera, María Paz (Anales de Psicología / Annals of Psychology, 2021)
The main objective of this research was to review the status of the psychopathological investigation of complicated grief in adult population of Spain. A systematic review on PsycINFO, PsycArticles, PTSDpubs, and PSICODOC databases identified 13 studies in which, overall, 1.655 adults had been evaluated. The results of this review show that there is no consensus in the diagnosis of complicated grief, in the use of detection instruments, or in the risk and protective factors for complicated grief. The weighted mean prevalence based on 6 of the reviewed studies was 21.53%. Taking into account the type of grief measurement used, a prevalence of 7.67-10.68% was obtained in those studies that used diagnostic instruments and 28.77% in the ones using symptomatic instruments. The results indicate that complicated grief is related to: a lower socioeconomic level and unfavorable work situation, the loss of a child or spouse, younger age of the deceased, previous psychological vulnerability, the use of psychotropic medication and comorbidity with other disorders. Social support, palliative care, problem-centered coping strategies, the use of pleasant activities, and transcendence or spirituality are shown as protective factors.